Back to Normal? Perspectives of Faculty and Teaching Librarians on Information Literacy Instruction After the Lockdowns - Baird, Catherine; Berg, Cara; Joachim, Anthony C.; Wallace, Drew (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2025)
Objective – While LIS scholars have extensively studied the widespread disruptions to library instruction during the lockdown period of the COVID-19 pandemic, there is a relative dearth of research concerning the longer-term implications for teaching information literacy (IL). This exploratory survey sought to examine how faculty have introduced IL skills to students before, during, and after the COVID-19 lockdowns. After returning to in-person operations in 2021, the authors observed a change in how faculty have engaged with libraries to teach IL to their students.Methods – Utilizing parallel survey instruments, we asked faculty and librarians for their perceptions of current and past practices with scheduling library IL sessions, evaluating student research skills and considering how they acquired those skills.Results – Although responses showed an unsurprising decrease in library instruction requests during the pandemic lockdowns, faculty respondents noted a return to nearly pre-pandemic norms after the resumption of in-person operations. Teaching modality and use of research assignments did not appear to impact faculty IL scheduling behaviors, but differences in faculty and librarian responses highlighted potential disagreements about the impact of COVID-19 on faculty use of library instruction. Additional questioning indicates a disconnect between how faculty perceive student research skills and their reasons for scheduling library instruction, which suggests misperceptions of librarian expertise and differences in understanding how librarians should teach information literacy. Open-ended responses provided additional context to these issues, while identifying potential barriers and opportunities.Conclusion – Overall, our findings indicate that, rather than fundamentally altering faculty approaches to information literacy, the COVID-19 disruptions revealed and exacerbated endemic problems with the prevalent one-shot model of library instruction.